(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The study examined the relationship between digital service marketing and sales performance of selected small enterprises in Uyo. The researchers adopted a survey research design in which primary data were obtained through questionnaire administration. The population of the study consisted of 200 small enterprises in Uyo, covering different sectors such as education, fashion, ICT, cosmetic, artisan, logistic, courier, and transportation. The sample size for the study was 133. The researchers employed tables and simple percentage method to analyse the research questions. However, Regression technique and Analysis of Variance (ANOVA) were used to test the hypothesis. The finding was that there is a significant relationship between digital service marketing and sales performance of selected small enterprises in Uyo. It was found that digital service marketing has influenced sales performance of selected small enterprises in Uyo positively and significantly. Recommendations were that there is need for provision of improved education on digital service marketing by small enterprises in Uyo. In order to improve sales performance of small enterprises in Uyo, there is need for all entrepreneurs to take advantage of more than one of the digital tools as part of service marketing strategies. The influence of digital service marketing on various sales levels should be monitored for appropriate policy drive towards ensuring sustainable success of small enterprises in Uyo among others.